Rot and revival the history of constitutional law in American political development - Kreis, Anthony Michael 1986- (University of California Press, 2024)
"Rot and Revival is one of the first scholarly works to comprehensively theorize and document how politics make American constitutional law and how the courts affect the path of partisan politics. Rejecting the idea that the Constitution's significance and interpretation can be divorced from contemporary political realities, Anthony Michael Kreis explains how American constitutional law reflects the ideological commitments of dominant political coalitions, the consequences of major public policy choices, and the influences of intervening social movements. Drawing on rich historical research and political science methodologies, Kreis convincingly demonstrates that the courts have never been-and cannot be-institutions lying outside the currents of national politics"--
Keywords: Constitutional history / United States; Constitutional law / United States; United States / Politics and government / History; Histoire constitutionnelle / États-Unis; États-Unis / Politique et gouvernement / Histoire; LAW / Constitutional; Constitutional history; Constitutional law; Politics and government; United States; History